Shifting cultivation and deforestation in Indonesia: steps toward overcoming confusion in the debate - Sunderlin, William D. (Overseas Development Institute, 1997)
The role of shifting cultivation in deforestation in Indonesia has been an area of great debate. Some claim this farming system is the main cause of forest cover loss. Others claim that - far from being damaging - it is a key means for the conservation and sustainable management of remaining forests. The two sides of the debate are talking past each other, because each refers to different farming systems at opposite ends of what might be called the 'forest farming continuum'. Recently, there has been progress in clarifying the meaning of certain terms but the debate remains confused. In order to better understand the causes and extent of forest cover change in Indonesia, it is necessary to clearly identify the different forms of agency affecting forests and also to define key terms and concepts such as 'forest', 'deforestation', 'degradation', and 'causation'. Based on these definitions an analysis of forest cover change over time can then be carried out.